Othello - Shakespeare, William, 1564-1616; Bloom, Harold (Shakespeare, William, 1564-1616. Works. 2003., 2005)
Presents William Shakespeare's dramatic tragedy in which Iago, jealous of Othello's successes in the army of Venice, plots against him, pretending to be his friend while planting seeds of doubt about the faithfulness of his wife, Desdemona; and includes text glosses, an introduction, details on the Shakespearean stage, an essay by critic Harold Bloom, and a further reading list.